Global Utilization of Online Information for Anxiety Disorders From 2004 to 2022: An Infodemiological Study of Google and Wikipedia - Rowalt Alibudbud (SAGE Open)
The utilization of online information can be used as a measure of public concern and interest. It can be explored to institute, inform, and innovate mental health promotion and strategies in addressing the ever-increasing prevalence of anxiety disorders across the globe. As such, this infodemiological study described and analyzed the public utilization of online information for anxiety disorders using relative search volumes (RSV), top and rising related queries and topics from Google Trends, and Wikipedia page views. After describing the data, autoregressive integrated mean averaging (ARIMA) models were employed to predict future RSVs and page views. Results show that RSVs for anxiety disorders have increased over the years and will further increase in succeeding years, while the use of Wikipedia information for anxiety disorders is declining. Top and rising search-related queries and topics primarily revolved around anxiety disorder concepts, management, manifestations, types, etiology, diagnostics, social consequences, and related mental disorders. Based on the search volumes, public utilization of online information about anxiety disorders has increased and will further increase in the coming years. They can be explained by the rising rates of anxiety disorder and the higher internet access across the globe. As such, the Internet is a promising medium for mental health promotion, prevention, and intervention strategies. Moreover, trustworthy and reliable online information about anxiety disorders is ever-crucial in this age of information and disinformation.